(untitled) (Academia Journal of Medicine, 2026)
Background: Post-extraction wound healing is an important determinant of patient comfort and successful oral rehabilitation. Platelet-Rich Fibrin (PRF), a second-generation platelet concentrate, has gained considerable attention because of its potential to accelerate soft-tissue healing and reduce post-operative complications due to the sustained release of growth factors. Aim: To comparatively evaluate post-extraction healing in extraction sockets treated with PRF and conventional healing following routine dental extraction. Materials and Methods: This randomized clinical study was conducted among 30 patients requiring bilateral extraction of comparable teeth. The patients were divided into two groups: Group I (PRF group), where PRF was placed into the extraction socket immediately after extraction, and Group II (control group), where extraction sockets were allowed to heal conventionally without any adjunctive material. Clinical parameters including pain, swelling, soft-tissue healing, and incidence of complications were assessed on the 1st, 3rd, and 7th post-operative days using standardized indices and visual analogue scale (VAS). The collected data were statistically analyzed using appropriate tests with significance set at p < 0.05. Results: The PRF group demonstrated significantly improved soft-tissue healing and reduced post-operative pain and swelling compared to the conventional healing group. Faster epithelialization and reduced incidence of complications such as dry socket were observed in sockets treated with PRF. Statistical analysis revealed significant differences between the groups, particularly on the 3rd and 7th post-operative days. Conclusion: Placement of PRF in extraction sockets enhanced post-extraction healing and improved patient comfort when compared with conventional healing. PRF can be considered a simple, cost-effective, and biologically acceptable adjunct for promoting wound healing following dental extraction.